Development of Porous Asymmetric Polyamide–Imide Torlon® Membranes for Physical CO2 Absorption and Separation - Sheikhi, S.; Mansourizadeh, A. (Journal of Membrane and Separation Technology, 2014)
Porous flat-sheet polyamide–imide (PAI) membranes were prepared via a phase inversion method to evaluate CO2 absorption performance in the gas-liquid membrane contactors. Different amounts of polyethylene glycol (PEG-600) were introduced into the polymer solution to investigate the structure and performance of resulted membranes. The membranes were characterized in terms of gas permeation, contact angle measurement and CO2 absorption flux. By introducing 6 wt.% PEG into the polymer dope, N2 permeance of the membrane was significantly improved from 482 to 1320 GPU. Mean while, the effect of PEG on the measured water contact angle was in significant. From CO2 absorption test, the developed membrane presented about 90% higher CO2flux compared to the plain membrane at water flow rate of 70 ml/min. In conclusion, by introducing a polymeric non-solvent additive into the polymer dope, it is possible to enhance surface porosity (permeability) of PAI membranes, which is a key factor for CO2 absorption test.